P-248 Care towards the end of life course for carers 'how people die remains in the memory of those who live on', dame cicely saunders. Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Hewitt, Claire; Kelly, Sharon
Abstract : Background: It has been evidenced 'By improving communication about the medical, practical, psychosocial, and religious/spiritual issues that surround death and dying will lead to caregivers being better prepared for the death and, as a result, improve their well-being' Herbert RS et al. (2009). Locally from completing the Carer Support Needs Assessment Tool (CSNAT) (Ewing & Grande, 2013), we are finding that the most common domain identified by carers and needing additional support is 'knowing what to expect in the future.' Therefore, in collaboration with carers in Hertfordshire and the Peace Hospice in 2013 the 'Care towards the End of Life Course for Carers' was developed to be run across both hospices. The Aim of the Course: To provide a safe forum to educate carers and provide support for those in a similar positon. To share experiences and build on their confidence, particularly in having difficult conversations. Methods: A six-week programme is delivered twice a year covering a range of relevant topics, each one developed further from feedback. We aim to have 12 people attend. Results: Forty-nine carers have attended the courses. 92% of carers were very satisfied with the content and delivery. Carers' feedback: 'The knowledge of understanding of what's to come'; 'That it is never too early but can be too late'; 'Reaffirmed that I am doing the right things and planning correctly.' Conclusions: The impact of the carer journey can significantly influence the bereavement process. The feedback supports the need of the course in providing information and support to carers who are who are caring for a person who is approaching their end of life. We have been contacted by other hospices who are interested in developing their carers' support services and have shared the course content and experiences with them.